2002
DOI: 10.1590/s0074-02762002000800005
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of T cell-activation molecules in response to Mycobacterium tuberculosis antigens

Abstract: The phenotypic features acquired subsequent to antigen-specific stimulation in vitro were evaluated by means of the kinetic expressions of CD69 and CD25 activation There has been a concentrated effort over the last few years to characterize specific Mtb molecules for inclusion in a novel TB vaccine and development of more efficacious diagnostic tools. Up to now, evaluations of the functional T cell response in vitro have been based on the secretion of cytokines (mainly IFNγ) and on the expression of activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
9
1
1
Order By: Relevance
“…In contrast to these studies, we showed that strain M did not inhibit TCR signaling and CD69 expression in CD8 + T cells even when this strain was present along the entire culture. In addition, we found no differences in the kinetic of CD69 expression, suggesting that its low expression is not due to a delayed CD8 + T cells activation caused by strain M, as it was observed with other mycobacterial antigens [30]; however, we can not rule out the involvement of other co-stimulatory molecules. Signaling trough CD69 controls IL-2 and IFN-γ gene expression at the transcriptional levels [45], [46] as well as Stat-5 mediated IL-2 signaling.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In contrast to these studies, we showed that strain M did not inhibit TCR signaling and CD69 expression in CD8 + T cells even when this strain was present along the entire culture. In addition, we found no differences in the kinetic of CD69 expression, suggesting that its low expression is not due to a delayed CD8 + T cells activation caused by strain M, as it was observed with other mycobacterial antigens [30]; however, we can not rule out the involvement of other co-stimulatory molecules. Signaling trough CD69 controls IL-2 and IFN-γ gene expression at the transcriptional levels [45], [46] as well as Stat-5 mediated IL-2 signaling.…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast CD25 expression was not modified (data not shown). Given that CD4 + and CD8 + T cells stimulated with mycobacterial antigens show delayed kinetic in CD69 and CD25 expression compared to PHA stimulation in PPD + N [30], we wondered if the low CD69 expression could be due to a delay in CD8 + T cells activation. Thus, the kinetics of CD69 and CD25 expression (1–5 d) in PBMC cultured with Mtb strains were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, evaluations of the functional T cell response in vitro have been based on the secretion of cytokines, mainly IFN-␥, and on the expression of activation molecules on the cell surface. 25 Testing peripheral blood for genetic markers that control the production of inflammatory cytokines such as IFN-␥ may be a better predictor of the outcome of vaccination with BCG. The association between IFN-␥ (ϩ874T/A) polymorphism and production of IFN-␥ by PBMC stimulated with Ag85A, observed in this study indicate the role of polymorphism within the cytokine gene as a marker for identifying individuals at risk for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In response to phytohaemagglutinin (PHA) stimulation in vitro, CD69 is an early T cell activation marker transiently expressed on T cells. CD69 expression occurs remarkably at 4 h, peaked at 24 h, and quickly decreased at 120 h (Antas et al, 2002). In vivo activation of T cells also induces expression of CD69.…”
mentioning
confidence: 98%